중공 구조 주얼리 제작을 통한 SLM방식 스테인리스(SUS316L) 3D 프린팅 공정 조건 연구 - 김희수; Kim Heesu; 김규현; Kim Kyu Hyun; 백경찬; Paik Kyung Chan; 송오성; Song Oh Sung; 주영창; Joo Young Chang; 최인석; Choi In-suk; et al. (기초조형학연구, 2023)
이 연구의 목적은 금속 3D프린터가 금속공예나 주얼리 분야에서 활용되기 위해 각 용도에 맞는 공정 조건을 도출하는 것이다. 분말적층용융(PBF) 방식의 금속 3D 프린팅 방법 중 하나인 선택적 레이저 용융(SLM) 공정은 금속분말을 레이저로 용융시킨 후 다시 굳히는 과정을 반복하며 적층 시키는 제조 방식으로서 정교하고 복잡한 형상을 가진 제품을 만들 수 있는 장점을 지닌다. 그러나 적층 과정 내 발생하는 급격한 가열 및 냉각은 공극 형성 및 미세구조 변화를 야기하는데, 이는 난발과 같은 부분의 강도 및 내구성을 저하시키는 주요한 원인이 될 수 있다. 연구방법은 스테인리스강 SUS316L 분말을 이용하여 다양한 레이저 출력과 주사 속도를 조절해 에너지밀도를 변화시켜 바뀐 값에 따른 상대밀도 값을 도출하는 방식으로 진행되었다. 이후 경도 및 인장시험을 통해 강도와 연성을 확인하였으며, 이를 통해 주얼리 작업에 최적화된 강도와 연성을 갖는 공정조건을 수립하였다. 연구결과 주조의 어려움으로 그동안 스테인리스를 사용한 주얼리는 디자인에 제한이 많았으나 PBF방식의 장점을 활용하여 서포트 없이 트러스들이 중공 구조를 이루어 기존의 정밀주조로는 제작이 어려운 주얼리 형상을 SLM 공정으로 출력할 수 있었다. 파우더기반인 SLM출력방식의 특성상 광택이 없는 출력물의 표면은 스레인리스 합금으로 경도가 높았으나 주얼리의 폴리싱도구를 통해 표면처리가 가능하였고 도출된 공정 조건을 통해 제작된 난발로 큐빅 지르코니아와 같이 경도가 높지 않은 스톤도 기존의 세공 도구를 사용하여 세팅할 수 있음을 확인하였다. The objective of this study is to explore process parameters appropriate for a wide range of applications in the use of metal 3D printers within the realms of metal craftsmanship and jewelry design. Selective Laser Melting (SLM), one of the metal 3D printing methods of the Powder Bed Fusion (PBF) approach, is a manufacturing technique that repeats the process of melting metal powder with a laser and then solidifying it. This allows for the creation of intricate and complexly shaped products. However, the rapid heating and cooling that occur during the layering process can lead to the formation of voids and changes in microstructure, which can be a major cause of decreased strength and durability in areas akin to defects. In this study, using stainless steel SUS316L powder, various laser outputs and scanning speeds were first adjusted to change the energy density, leading to different relative densities. Subsequently, the strength and ductility were confirmed through hardness and tensile tests, and through this, processing conditions optimized for jewelry crafting, possessing the desired strength and ductility, were established. Until now, jewelry made of stainless steel has been limited in design due to the difficulties in casting. However, in this study, by utilizing the advantages of the PBF method, it was possible to create jewelry shapes that were previously difficult to produce using traditional precision casting methods, with trusses forming a hollow structure without the need for supports in the SLM process. Due to the nature of the powder-based SLM printing method, the surface of the output lacks gloss, but it had high hardness thanks to the stainless alloy. Surface treatment was achievable using jewelry polishing tools, and it was confirmed that even stones with low hardness, such as cubic zirconia, could be set using traditional setting tools with the process conditions obtained through this study.